The diversity of microfungi associated with grasses in the Sporobolus indicus complex in Queensland, Australia - Steinrucken, Tracey V.; Vitelli, Joseph S.; Holdom, David G.; Tan, Yu Pei (Frontiers in Fungal Biology, 2022)
There are five closely related Sporobolus species, collectively known as weedy Sporobolus grasses (WSG) or the rat’s tail grasses. They are fast growing, highly competitive, unpalatable weeds of pastures, roadsides and woodlands. An effective biological control agent would be a welcomed alternative to successive herbicide application and manual removal methods. This study describes the initial exploratory phase of isolating and identifying native Australian microfungi associated with WSG, prior to evaluating their efficacy as inundative biological control agents. Accurate species-level identification of plant-pathogenic microfungi associated with WSG is an essential first step in the evaluation and prioritisation of pathogenicity bioassays. Starting with more than 79 unique fungal morphotypes isolated from diseased Sporobolus grasses in Queensland, Australia, we employed multi-locus phylogenetic analyses to classify these isolates into 54 fungal taxa. These taxa belong to 22 Ascomycete families (12 orders), of which the majority fall within the Pleosporales (>24 taxa in 7 families). In the next phase of the study, the putative species identities of these taxa will allow us to prioritise those which are likely to be pathogenic based on existing literature and their known ecological roles. This study represents the first step in a systematic, high-throughput approach to finding potential plant pathogenic biological control agents.